A new class of anomeric spironucleosides - Gimisis, Thanasis; Castellari, Carlo; Chatgilialoglu, Chryssostomos; Gimisis, Thanasis; Castellari, Carlo (Chem. Commun., 1997)
A 1,5-hydrogen migration of a conveniently situated alkoxyl radical affords spironucleosides which possess an unusual orthoamide structure at the anomeric position; X-ray crystallography establishes the configuration of the C-1' position.